Analisis Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Konsumen Pada Uber Taxi Di Surabaya - Chusniati, Yeni; Maruta, Anom; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2017)
in the business world have started a lot of competition, especially in the field of transport. In each competition, many business people do way or a better strategy in order to meet the needs of consumers as well as provide satisfaction to the maximum, and to give the best service. Formulation of the problem in this research is to 1) If quality of service effect on consumer satisfaction Uber taxi? 2). Does the facility have an effect on consumer satisfaction Uber taxi?. The purpose of doing research is to know the influence of 1). The quality of service of consumer satisfaction Uber taxi, 2). Facilities against consumer satisfaction Uber taxi. this research use descriptive research type with quantitative approach. Method of quantitative research is research that is based on the philosophy of positivism, used for researching on population or a particular sample, data collection using the instruments of research, data analysisquantitative in nature.the results and conclusions of this research is to 1). Quality of service in a positive effect on consumer satisfaction 2). Facilities positively influential on consumer satisfaction. Recommendations is given to the management of the company to always improve the quality of services such as paying attention to consumers, to the employees of the uber taxi to create quality good service (friendliness, polite – courteous, speed), to increase consumer satisfaction need any additional value offered. keywords: service quality, facilities and customer satisfaction